2005
DOI: 10.1111/j.1365-2621.2004.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition, quality control and antimicrobial activity of the essential oil of cumin (Cuminum cyminum L.) seeds from Bulgaria that had been stored for up to 36 years

Abstract: The essential oil of seeds of cumin (Cuminum cyminum L.) from Bulgaria stored for more than 35 years was analyzed by physicochemical methods, GC, GC-MS and olfactometry and its antimicrobial activity tested using different strains of microorganisms. More than sixty constituents of this cumin oil could be identified as essential volatiles, responsible for the pleasant fresh, clean, spicy (typical cumin-like) odour of a high quality product. Cumin aldehyde (36%), b-pinene (19.3%), p-cymene (18.4%) and c-terpinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 10 publications
9
44
0
1
Order By: Relevance
“…For instance, the oil contents obtained 3.8% from China (Li and Jiang, 2004), 5.3% from Bulgaria (Jirovetz et al, 2005), 1.6% from Tunisia (Rebey et al, 2012), and 1.4-2.2% from Northeastern Iran (Hashemian et al, 2013).…”
Section: Essential Oil Yieldmentioning
confidence: 97%
“…For instance, the oil contents obtained 3.8% from China (Li and Jiang, 2004), 5.3% from Bulgaria (Jirovetz et al, 2005), 1.6% from Tunisia (Rebey et al, 2012), and 1.4-2.2% from Northeastern Iran (Hashemian et al, 2013).…”
Section: Essential Oil Yieldmentioning
confidence: 97%
“…The essential oil of Bulgarian Cuminum cyminum was active against Aspergillus niger, Bacillus subtilis, Staphylococcus epidermidis, Saccharomyces cerevisiae and Candida albicans [198].…”
Section: Cyminum Cuminummentioning
confidence: 99%
“…It is also used to inhibit the fibrillation of alpha-synuclein (α-SN), 52 Parkinson's disease and viral infections. Cuminaldehyde has shown different effects such as anti-platelet, 53 antibacterial, 3 antifungal, 54 anti-diabetic, 55 anti-Parkinson's 56 and it also activates salivary glands in mouth and facilitates the primary digestion of the food and produce carminative effects. Cuminaldehyde has been under study to verify its effectiveness as an antitumor agent and has shown good results on cultured murine but not on cultured human cells.…”
Section: Components Of Cuminmentioning
confidence: 99%
“…Cuminaldehyde (4 -isopropyl benzaldehyde) is an aromatic monoterpenoid volatile compound and a constituent of the essential oils of eucalyptus, myrrh, Cuminum cyminum, 3 Carum carvi, 8,47 Cinnamomum cassia 51 and others. 8,17 Cuminaldehyde has molecular formula C 10 H 12 O that is a substitute of benzaldehyde with an isopropyl group in the 4 th position.…”
Section: Components Of Cuminmentioning
confidence: 99%